The return of the Indian: indigenous historiography in Canada in the second half of the 20th century - Beaucauge, Pierre (Revista de Historia Social y de las Mentalidades, 2013)
The development of indigenous historiography in Canada during the second half of the 20th century is addressed, a development that goes hand in hand with the country's indigenous social movements; In this sense, the relationship between national history and the "New Indigenous History" is analyzed. The article also presents the four aspects on which the current debate on the subject is focused.
Keywords: Historiografía indígena; movimiento social; movimiento indígena